Pelatihan Deteksi Skoliosis Dan Excercise Skoliosis Terhadap Tingkat Pengetahuan Bagi Seluruh Fisioterapis Puskesmas Karanganyar Dan Surakarta - Sugiono, Sugiono; Noerdjanah, Noerdjanah (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2024)
Background: Physically healthy, one of which is the absence of changes in the curvature of the spine in a person. Changes in the curvature of the spine if measured and as early as possible can provide information to the patient and family that there is a curvature of the spine, so that further treatment can be given to prevent the occurrence of a greater degree of curvature of the spine so that it does not experience more severe deformity. Therefore, it is necessary to increase promotive and preventive knowledge of preventing scoliosis or spinal curvature disorders to physiotherapists. Physiotherapists in Karanganyar and Surakarta. Objective: To increase knowledge of scoliosis detection and scoliosis exercises towards the level of knowledge for all physiotherapists at Karanganyar and Surakarta health centers. Benefits: Knowledge of scoliosis detection and scoliosis exercises for all physiotherapists at Karanganyar and Surakarta health centers can be increased so that the expertise of physiotherapists in promotive and preventive measures related to scoliosis detection and scoliosis exercises can be applied to the community. Method: Training related to scoliosis detection and scoliosis exercises using lecture, discussion and demonstration methods, provision of brochures to physiotherapists in 20 Health Centers in Karanganyar Regency and Physiotherapists in 5 Health Centers in Surakarta City, before and after training, physiotherapists were given questions to determine the level of understanding before and after training. Place and time: Training in Karanganyar Regency Campus 2 Poltekkes Kemenkes Surakarta February - November 2023. Output: the results obtained were an increase in knowledge for physiotherapists in Karanganyar and Sukakarta health centers.